2015
DOI: 10.1007/s11064-015-1776-x
|View full text |Cite
|
Sign up to set email alerts
|

The Lipoxygenases: Their Regulation and Implication in Alzheimer’s Disease

Abstract: Inflammatory processes and alterations of lipid metabolism play a crucial role in Alzheimer’s disease (AD) and other neurodegenerative disorders. Polyunsaturated fatty acids (PUFA) metabolism impaired by cyclooxygenases (COX-1, COX-2), which are responsible for formation of several eicosanoids, and by lipoxygenases (LOXs) that catalyze the addition of oxygen to linolenic, arachidonic (AA), and docosahexaenoic acids (DHA) and other PUFA leading to formation of bioactive lipids, significantly affects the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 147 publications
2
57
0
1
Order By: Relevance
“…Lipoxygenases are enzymes containing non-heme iron and requiring catalytic activation. This activation process involves transformation of non-active iron in ferrous state to iron in ferric state, and this is accomplished by lipid hydroperoxide oxidation [4]. Several independent studies now support the correlation between 5-LOX expression and cancer cell viability, proliferation, cell migration, invasion through extracellular matrix destruction, metastasis, and activation of anti-apoptotic signaling cascades [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipoxygenases are enzymes containing non-heme iron and requiring catalytic activation. This activation process involves transformation of non-active iron in ferrous state to iron in ferric state, and this is accomplished by lipid hydroperoxide oxidation [4]. Several independent studies now support the correlation between 5-LOX expression and cancer cell viability, proliferation, cell migration, invasion through extracellular matrix destruction, metastasis, and activation of anti-apoptotic signaling cascades [26].…”
Section: Resultsmentioning
confidence: 99%
“…Oxygenation of polyunsaturated fatty acids containing a (cis, cis)-1,4-pentadiene system is catalyzed by lipoxygenases (LOXs). The main substrates for LOXs are arachidonic and docosahexaenoic acids released from membrane phospholipids by phospholipases A2 (PLA2) [3,4]. Evidence is accumulating in support of the direct involvement of 5-LOX in the progression of different types of cancer, including prostate, lung, colon, and colorectal cancers [5], (i) a given activity of phenolic compounds studied in vitro (after their isolation from the food) does not have to be in accordance with the same activity demonstrated in the human organism [13].…”
Section: Introductionmentioning
confidence: 99%
“…Arachidonic acid metabolism is catalyzed by cyclooxygenase (COX) and lipoxygenase (LOX). As a result of oxidation of arachidonic acid by COX, a group of prostanoids is formed, while in LOX-catalyzed reactions, leukotrienes, as well as hydroxyeicosatetraenoic acid (HETE), are generated Figure 5 [85]. The resulting compounds, especially those belonging to the eicosanoids: prostaglandins, leukotrienes, thromboxanes, and HETE derivatives show multidirectional effects, mainly associated with the regulation of immune cell function and the modulation of inflammation.…”
Section: Eicosanoidsmentioning
confidence: 99%
“…Post‐mortem analysis of AD patients revealed upregulation of 12/15 LOX and increased levels of the LX precursors 12‐HETE and 15‐HETE in the frontal and temporal lobes . These findings are corroborated by another study which showed increase of the same precursors in cerebrospinal fluid of AD patients, as well as at‐risk patients with mild cognitive impairment, suggesting 12/15 LOX may be involved in the initiation of AD . However, another study has also demonstrated strongly reduced expression and activity of 15‐LOX in the hippocampus of AD patients compared to the hippocampus of matched postmortem controls…”
Section: Lox Enzyme Dysregulation In Admentioning
confidence: 64%